Intonation processing deficits of emotional words among Mandarin Chinese speakers with congenital amusia: an ERP study - Lu, Xuejing; Ho, Hao Tam; Liu, Fang; Wu, Daxing; Thompson, William F. (Frontiers in Psychology, 2015)
Background: Amusia is a disorder that is known to affect the processing of musical pitch. Although individuals with amusia rarely show language deficits in daily life, a number of findings point to possible impairments in speech prosody that amusic perceivers may compensate for by drawing on linguistic information. Using EEG, we investigated (1) whether the processing of speech prosody is impaired in amusia and (2) whether emotional linguistic information can ease this process. Method: Twenty Chinese amusics and 22 matched controls were presented pairs of emotional words spoken with either statement or question intonation while their EEG was recorded. Their task was to judge whether the intonations were the same. Results: Emotional linguistic information did not facilitate amusics’ performance on the intonation-matching task, as their performance was significantly worse than that of controls. EEG results showed a reduced N2 response to incongruent intonation pairs in amusics compared with controls, which likely reflects impaired conflict processing in amusia. However, at an “earlier” processing stage, our EEG results indicate that amusics were intact in early sensory auditory processing, as revealed by a comparable N1 modulation in both groups. Conclusion: We propose that the impairment in discriminating speech intonation observed among amusic individuals may arise from an inability to access information extracted at early processing stages. This, in turn, could reflect a disconnection between low-level and high-level processing.